El argumento de la existencia de Dios en la Monadología - Vargas Elizondo, Celso (2014)
In this paper is presented a proposal to understand Leibniz’s claim that in the case of God, “...essence includes existence; meaning that in the case of God being possible is sufficient for being actual”. This modal argument is grounded in the equivalence between three general groups of arguments: those referred to the different levels of perfection that exhibit our world, the used of the principle of sufficient reason and the depicted world that results from the principles of plenitude, linear graduation and continuity. That is the same conclusion follows deductively (a priori), inductively and abductively. But before introducing this analysis (in the second section) it is important to offer some way of classifying the types of arguments to prove the existence of God. This is objective of the first section. In the third I present some additional arguments related with the kind of world depicted by Leibniz.